Peripheral mast cells derive the effects of acupuncture in Parkinson’s disease - Oh, Ju-Young; Bae, Sun-Jeong; Ji, Jeong-Yeon; Hwang, Tae-Yeon; Ji, Suhwan; Park, Ji-Yeun; Kim, Seung-Nam; Ryu, Yeonhee; Nam, Min-Ho; Park, Hi-Joon (Frontiers in Aging Neuroscience, 2024)
This research investigates the peripheral mechanisms of acupuncture in treating Parkinson’s disease (PD), a progressive neurodegenerative disorder marked by motor impairments. While the central mechanisms of acupuncture have been extensively studied, our focus lies in the peripheral mechanisms at the acupoints, the sites of acupuncture signal initiation. Employing a PD model, we analyzed the local responses to acupuncture stimulation at these points. Our key finding was a significant elevation in both the number and activity of mast cells (MCs) in the peripheral tissues following acupuncture. Intriguingly, pre-treatment with an MC stabilizer diminished the acupuncture’s therapeutic effects on PD symptoms. Similarly, local anesthesia with lidocaine at the acupoints attenuated the symptom improvement typically observed with acupuncture. Meanwhile, the augmentation of MC activity induced by acupuncture was significantly impeded by cromolyn, an MC stabilizer, but remained unaffected by lidocaine. This finding suggests that MC activity is a more upstream regulator of acupuncture effects compared to nerve conduction. This study provides groundbreaking insights into the initiation and transmission of acupuncture signals, highlighting the significant role of peripheral MC modulation in PD treatment.